PERCEIVED QUALITY DAN PRICE TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN APOTEK KARANGGEDE DENGAN BRAND AWARENESS SEBAGAI VARIABEL INTERVENING - Takri Ul Vuad; Bambang Mursito; Ida Aryati (JURNAL ILMIAH EDUNOMIKA, 2020)
The research purposes were testing and analysis the effect of perceived quality and price to the purchasing decision of Apotek Karanggede customers with brand awareness as intervening variable.The research type is explanatory research. The research population are Cutomers of Apotek Karanggede. Sampling technique was used purposive sampling technique. Data collection was used questionnaires. Data analysis techniques were used statistical analysis including of multiple linear tests, F-test, and t-test. The research results were shown that 1) Perceived quality significantly effect the brand awareness of Apotek Karanggede customers; 2) price significantly effect the brand awareness of Apotek Karanggede customers; 3) Perceived quality significantly effect the purchasing decision of Apotek Karanggede customers; 4) Price significantly effect the purchasing decision of Apotek Karanggede customers; 5) Brand awareness significantly effect the purchasing decision of Apotek Karanggede customers; 6) Brand awareness are able as intervening variabel in the effect of perceived quality to the purchasing decision of Apotek Karanggede customers; and 7) Brand awareness are able as intervening variabel in the effect of price to the purchasing decision of Apotek Karanggede customers Keywords: perceived quality, price, brand awareness, purchasing decision